Pengaruh Content Marketing Instagram, Social Media Marketing Instagram, Price, Dan Restaurant Atmosphere Terhadap Repurchase Intention Pada Restaurant Dan Bar - Gregorius Edwin Yonathan; Innocentius Bernarto (At-Tadbir : jurnal ilmiah manajemen, 2022)
This research is motivated by whether or not there is a relationship between the variables of Instagram content marketing, Instagram social media marketing, price, and restaurant atmosphere on repurchase intention. This study aims to analyze the effect of the variables of Instagram content marketing, social media marketing Instagram, price, and restaurant atmosphere on repurchase intention in restaurants and bars. The research method used is a causal research method. This research method is used to test whether a variable causes changes in other variables or not. This research was conducted on 384 consumers at restaurants and bars in South Jakarta. Respondents were selected from the sample of interest and data were collected using a Likert Scale questionnaire which was distributed online and offline. PLSSEM was used to analyze the data. The results show that Instagram content marketing, Instagram social media marketing, price, and restaurant atmosphere affect repurchase intention at Restaurants and Bars in South Jakarta positively and significantly, so there are no variables that have no effect. Further research can be carried out with qualitative analysis using the interview method to find out more about the reasons for consumers to repurchase.